PENGEMBANGAN GAME 3D “EVERPLANE” DENGAN LEAP MOTION - Galang Ihsan Isnanto; Samuel Gandang Gunanto; Agnes Karina Pritha Atmani (Institut Seni Indonesia Yogyakarta, 2019)
Motion Leap (Hand Motion tracking) is a term for recording hand movements used as digital models and is an additional device that can be connected to a computer and can then be used to replace both mouse and keyboard functions. In the 3D game